ANALISIS KUALITAS PERAIRAN SUNGAI RAMAN DESA PUJODADI TRIMURJO SEBAGAI SUMBER BELAJAR BIOLOGI SMA PADA MATERI EKOSISTEM - Sutanto, Agus; Purwasih, Purwasih (BIOEDUKASI (Jurnal Pendidikan Biologi), 2015)
River is one of fresh water ecosystem which is very important in human life since it is the most practical and economical source in fulfilling domestic and industrial needs. Therefore, it should meet the quality standards. The research objectives were: 1) knowing the quality of waterway in Raman River, Pujodadi, Trimurjo, based on the physical, chemical and biological aspects; 2) turning the information intoa Biology learning source on Ecosystem subject. The data were directly observed in the river by measuring the physical factors (temperature, stream, turbidity); chemical factors (pH, DO); and biological factor (macro invertebrates). The results were: temperature 24-29oC ; stream 0.3 – 0.6 mm/s; turbidity 33.5-3.7 NTU; pH 4.1-5.2; and DO 2.07-2.35 ml/I. Furthermore, micro vertebrates found were; a) Plecoptra; b) Tricoptra; c) Mollusca, d) Ephemeroptra; and e) Hemiptra. In each station, they were classified as insects and non-insects. The insects found were: 1) Odonata; 2) Tricoptra; 3) Ephemeroptra; 4) Plecoptra. Based on those parameters, the waterway quality was qualified as light wasted. The results can be turned into student worksheet as a Biology learning source, especially on Ecosystem subject.